St. Anne’s collegiate in Kraków as a geotouristic site - Florczyk, Monika; Smoleńska, Anna (Geotourism/Geoturystyka, 2025)
The authors aim at drawing the attention of tourist not only to the history and architecture of St. Anne’s collegiate church in Kraków, one of the most beautiful Baroque structures in Poland. The particular aspect they focus on refers to the decorative valour of the stones, which in large numbers and an attractive manner have been used inside and outside the church. As an addition to the description of the rock types and their varieties used, the places of quarrying the respective stones have been indicated for those interested in geology.